Carbapenem-resistant Gram-negative bacteria – analysis of the data obtained through a mandatory reporting system in the Rhine-Main region, Germany, 2012–2015 - Heudorf, Ursel (GMS Hygiene and Infection Control, 2016)
Background: Multidrug-resistant Gram-negative bacteria (MRGN) and the infections they cause are a serious threat and a challenge to the healthcare system. This particularly applies to carbapenem-resistant Gram-negative bacteria (CRGN). Currently, the introduction of a nationwide mandatory notification system for CRGN in Germany is under consideration. Against this background, this paper presents an analysis of the mandatory reporting system for CRGN in effect since November 2011 in the federal state of Hesse (Germany). Materials and methods: All carbapenem-resistant Gram-negative bacteria and the detected carbapenemases reported to the public health department of the city of Frankfurt am Main, Hesse, Germany, on the basis of the mandatory notification system were analyzed.Results: 827 CRGN cases were reported to the public health department of Frankfurt/Main between April 2012 and December 2015. The following bacterial species were reported: spp. (n=268), spp. (n=183), spp. (n=195), spp. (n=77), (n=75) and others (n=29). Between 2012 and 2015, a reduction of the CRGN reports was noticed, mainly due to changes in the reporting of spp. Between 2012 and 2015, the total number of notifications decreased slightly, although the number of reported CRGN in screening samples increased, thus giving no indication of a decreased testing frequency. For 10.5% of the patients, the place of residence was not Germany, 18.0% of the patients had previously stayed in hospitals abroad, often in countries with a high CRGN prevalence. CRGN bacteria were reported from all of Frankfurt’s hospitals, and 3.9% were reported from out-patient care facilities. Carbapenemases were detected and reported in 251 CRGN bacteria, including 73 OXA-48, 76 OXA-23, 56 NDM subtypes, and 21 KPC subtypes. There have been no major epidemiological signs of outbreak scenarios.Discussion: CRGN bacteria are already widespread in patients from hospitals and out-patient care facilities. Clearly, infection control measurements should therefore not only include hospital patients but also those receiving out-patient care. Screening strategies focused on patients from foreign countries with high MRGN prevalence is not sufficient, as only 10.5% of MRGN patients resided in those countries, and only 18% of the patients had been previously treated in a foreign hospital. In a public health context, infection control measures should therefore encompass broader screening strategies.